Synthesis, Characterization, and Antioxidant Activity Evaluation of New N-Methyl Substituted Thiazole-Derived Polyphenolic Compounds - Alexandra Cătălina Cornea; Gabriel Marc; Ioana Ionuț; Cristina Moldovan; Anca Stana; Smaranda Dafina Oniga; Adrian Pîrnău; Laurian Vlase; Ilioara Oniga; Ovidiu Oniga (Molecules)
Reactive oxygen species play a significant role in various pathological conditions, driving the need for novel, potent antioxidants. While polyphenols are known for their antioxidant properties, their limited stability and bioavailability present challenges for therapeutic applications. To address these limitations, a series of novel thiazolyl-polyphenolic compounds was synthesized via a multi-step synthetic route incorporating Hantzsch heterocyclization in the final step. The synthesized compounds 7a–k were structurally characterized using spectroscopic techniques, including NMR, MS, and IR. In silico thermodynamic calculations, including HOMO–LUMO gap and bond dissociation enthalpy (BDE) calculations, revealed a promising antioxidant profile for these compounds and indicated that the substitution in position 2 of the thiazole ring does not substantially influence the antioxidant activity conferred by the catechol moiety in position 4. The antioxidant capacity of the synthesized compounds was experimentally validated using a panel of six distinct assays: two radical scavenging assays (ABTS and DPPH) and four electron transfer-based assays (RP, TAC, FRAP, and CUPRAC). The in vitro evaluation demonstrated that compounds 7j and 7k exhibited significantly enhanced antioxidant activity compared to the established antioxidant standards, ascorbic acid and Trolox. These findings suggest that the strategic modifications in position 2 of the thiazole scaffold represent a promising direction for future research aimed at developing novel therapeutic agents with enhanced antioxidant properties. The present study is limited to the in vitro evaluation of compounds based on the N-methyl substituted thiazole scaffold, but future studies can include modifications such as changing the substituent on the thiazole nitrogen, the hydrazone linker or possible insertion of substituents in position 5 of thiazole ring of substituents with various electronic or physico-chemical properties.